Periode Kritis Perkembangan Tanaman Padi terhadap Penyakit Hawar Pelepah (Rhizoctonia solani) dan Pengaruhnya terhadap Hasil - Milati, Laila Nur; Nuryanto, Bambang (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Sheath blight disease, one of the most important diseases in rice, is caused by the fungus Rhizoctonia solani. The aim of the study was to find out the response of rice plant in different growth stages against R. solani infection. This research was performed during the dry and rainy seasons of 2017. The experiment used split plot design with four replications. The main plot was rice varietie (Ciherang, Minghui 63, and Hipa Jatim 2) and the sub plot was the inoculation times (maximum tillering, panicle initiation, flowering, and ripening). Rice cultivation wasperformed following the farmers practiceon 1000m2 areas devided by 60 experimental plots, 3m x 5m each. Data analysis and interpretation were performed using scatter chart and SAS 9.0. The results showed that sheath blight developed significantly and affected area under the disease progress curve (AUDPC) during maximum tillering (56,67% in dry season and 56,02% in rainy season) and panicle initiation stages (79,07% in dry season and 56,85% in rainy season). The larger the AUDPC the higher the decrease in the rice production.Â